Coupling between Histone Conformations and DNA Geometry in Nucleosomes on a Microsecond Timescale: Atomistic Insights into Nucleosome Functions. Issue 1 (16th January 2016) - Shaytan, Alexey K.; Armeev, Grigoriy A.; Goncearenco, Alexander; Zhurkin, Victor B.; Landsman, David; Panchenko, Anna R.
Abstract: An octamer of histone proteins wraps about 200 bp of DNA into two superhelical turns to form nucleosomes found in chromatin. Although the static structure of the nucleosomal core particle has been solved, details of the dynamic interactions between histones and DNA remain elusive. We performed extensively long unconstrained, all-atom microsecond molecular dynamics simulations of nucleosomes including linker DNA segments and full-length histones in explicit solvent. For the first time, we were able to identify and characterize the rearrangements in nucleosomes on a microsecond timescale including the coupling between the conformation of the histone tails and the DNA geometry. We found that certain histone tail conformations promoted DNA bulging near its entry/exit sites, resulting in the formation of twist defects within the DNA. This led to a reorganization of histone–DNA interactions, suggestive of the formation of initial nucleosome sliding intermediates. We characterized the dynamics of the histone tails upon their condensation on the core and linker DNA and showed that tails may adopt conformationally constrained positions due to the insertion of "anchoring" lysines and arginines into the DNA minor grooves. Potentially, these phenomena affect the accessibility of post-translationally modified histone residues that serve as important sites for epigenetic marks (e.g., at H3K9, H3K27, H4K16), suggesting that interactions of the histone tails with the core and linker DNA modulate the processes of histone tail modifications and binding of the effector proteins. We discuss the implications of the observed results on the nucleosome function and compare our results to different experimental studies. Graphical abstract: Highlights: Mononucleosome dynamics is the key to decipher the chromatin function and epigenetic regulation. All-atom dynamics of full nucleosome with DNA linkers is probed on the microsecond timescale. Coupling between DNA geometry and reorganization of the histone–DNA interactions is observed. DNA bulging and twist-defect formation are detected near the entry/exit site, suggestive of nucleosome sliding mechanisms. Accessibility of important epigenetically modified sites is governed by the patterns of histone tails adsorption on both core and linker DNA.